Nonvenomous Snakebite in Pediatric Age Group—Wolf under a Sheep's Coat - Ranjit Kumar Sahu; Sourabh Shankar Chakraborty; Suresh K.; Sourabh Gupta (Indian Journal of Plastic Surgery)
Nonvenomous snakebite, far outnumbering venomous bites, is a neglected occupational hazard in the Indian subcontinent. We encountered four cases of traditionally nonvenomous snakebite in pediatric age group with symptoms of limb swelling proximal to the bite site. All cases were found to have extensive fibrinous exudate and fibrinoid necrosis of the deeper layer of fat, deep to the intact skin and superficial layer of fat, extending far from the wound toward the proximal limb in continuity. This obscured presentation of infection and extensive necrosis of only the deeper layer of fat warrants exploratory incisions proximally for thorough debridement, underlying the normal appearing skin.